Evaluasi Kapasitas Ruas Jalan Pantura Kabupaten Brebes - Untoro Nugroho; Agung Sutarto; Fenty Endradew; Yuliana Nur Alisa (Jurnal Teknik Sipil dan Perencanaan)
Brebes is one of the districts traversed by the road north coast. Congestion on roads pantura frequent because this road is a national road along the coast of the island of Java. Long road pantura Brebes 32.8 Km. The purpose of this study was to evaluate the capacity of roads pantura Brebes based on the volume of traffic there and know how big the relationship between the ratio of volume per capacity and traffic jams that occur on the road north coast Brebes. This research was conducted along the northern coast Brebes district. The data used are the characteristics data, inventory data path, the data traffic volume and vehicle speed data. Analysis was conducted on the Analysis of Traffic Volume, capacity analysis segment, analysis of vehicle speed, intersection capacity analysis, the analysis of the degree of saturation, analysis level of service redesign and analysis of road.